2016
DOI: 10.1515/ijamh-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

External criticism by parents and obsessive beliefs in adolescents in Iran: the mediating role of emotional self-regulation

Abstract: Background: Obsessive-compulsive disorder (OCD) is considered to be a significant impairment in childhood and adolescence. According to cognitive theories, parents' external criticism and emotional self-regulation are among the variables that can directly or indirectly affect obsessive beliefs. Objective: The present study aimed to examine the mediating role of emotional self-regulation in the relationship between parents' external criticism and obsessive beliefs in adolescents. Methods: In this study, 547 hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…According to cognitive theory (29), perceived criticism and strict parenting practices are considered as detrimental factors in the development of obsessive tendencies such as tobacco use. Besides, studies have revealed that the impact of criticism by parents on smoking in adolescents can be affected by cognitive-emotional factors (26,30) resulting in high-risk behaviors and cravings towards smoking (31).…”
Section: Discussionmentioning
confidence: 99%
“…According to cognitive theory (29), perceived criticism and strict parenting practices are considered as detrimental factors in the development of obsessive tendencies such as tobacco use. Besides, studies have revealed that the impact of criticism by parents on smoking in adolescents can be affected by cognitive-emotional factors (26,30) resulting in high-risk behaviors and cravings towards smoking (31).…”
Section: Discussionmentioning
confidence: 99%
“…Parents have been implicated in several studies on OCD in youth. For example, in one study on 547 adolescents entitled "External criticism by parents", emotional self-regulation and external criticism explained 47% of the variance in obsessive beliefs (Halvaiepour et al, 2016). These data are based on the Obsessive Beliefs Questionnaire.…”
Section: Family Prevalencementioning
confidence: 99%
“…Lack of care and proper education cause approximately 250 million under‐five children in lower socioeconomic countries to suffer from insufficient development . The great body of empirical research reveals that poor psycho‐emotional environment as well as adverse health care and education conditions during childhood have long‐term negative implications in terms of both poor adult health and adverse socioeconomic outcomes …”
Section: Introductionmentioning
confidence: 99%